Organizing water education regionally: the innovations, experiences and challenges of three southern water networks - Rap, Edwin; Prakash, A.; Zwarteveen, M.Z. (2013)
The paper presents and contrasts the experiences and challenges of three Regional Water Education Networks in Integrated Water Resources Management (IWRM) - WaterNet (Southern and Eastern Africa), Crossing Boundaries (South Asia) and Concertacion (Andes, Latin America). These continental water networks emerged in the new millennium primarily out of dissatisfaction with traditional North-South development and scientific cooperation. Rather than concentrating on centres of excellence that provide universal one-size-fits-all-models, these regional networks of knowledge centres set out to develop a contextual knowledge base on water resources management and build capacity in accordance with regional training needs. These collaborative partnerships have now gained experience in training a new generation of water professionals, who have learnt to appreciate the regional diversity in water problems and design relevant solutions for their regions, often in cooperation with local stakeholders. In this paper, we document and discuss the experiences of these regional networks, focusing especially on the networks' different approaches to 1) interdisciplinary and gender approaches, 2) the connection between capacity development, research and policy advocacy.